From a Molecular Toolbox to a Toolbox for Photoswitchable Fluorescent Polymeric Nanoparticles. (1st October 2018) - Yu, Maolin; Zhang, Peisheng; Krishnan, Baiju P.; Wang, Hong; Gao, Yong; Chen, Shu; Zeng, Rongjin; Cui, Jiaxi; Chen, Jian
Abstract: Switchable organic fluorescent materials are attracting much interest in many fields including flexible display, information storage, anti‐counterfeit, and bioimaging, due to their prominent properties and relatively low cost. Herein, a class of novel photoswitchable fluorescent polymeric nanoparticles (PFPNs) toolbox that shows switchable full‐colored emission including white light is described. This nanoparticles toolbox consists of a series of reversibly photoswitchable and non‐PFPNs with red, green, and blue fluorescence, and is built up from three primary fluorescent dyes and a photochromic diarylethene molecule, through a facile one‐pot miniemulsion method. The as‐prepared PFPNs display the merits of high fluorescence resonance energy transfer efficiency and fluorescence quantum yield, rapid responsiveness, prominent photoreversibility, and brilliant long‐term fluorescence stability (≈ 6 weeks). They enable switchable emission between white light and any visible color on‐demand in both solution and film states. Their potential in complex fluorescent encryption and photoswitchable white light‐emitting diode is described and its great potential in anti‐counterfeiting technology, data encryption, and the next generation of optoelectronic materials is foreseen. Abstract : A full‐colored photoswitchable fluorescent polymeric nanoparticle (PFPN) toolbox is built up via the preparation of a series of reversibly photoswitchable and non‐PFPNs based on three primary fluorescent dyes and a photochromic diarylethene molecule. By varying the mixture ratio of the nanoparticles, the mixed PFPNs‐based nanoparticle solution or film displays photoswitchable fluorescence from white‐light to full‐colored fluorescence.